ETIKA BIOTEKNOLOGI MODERN - Kusmaryanto, Carolus Borromeus (Jurnal Orientasi Baru, 2016)
Our modern life cannot be separated from biotechnology because biotechnology affects all of our lives and has altered everything we encounter in life. What we eat everyday and most of the medicines to cure our illness are the products of biotechnology. The rapid development of biotechnology in modern era creates various ethical problems. When it is applied to human beings, it creates the hardest ethical problem that cannot be resolved easily, while most of non human being biotechnology creates ethical problem which can be resolved if rigorously applied. Both of them need prudence and clear ethical guidance and principles which is provided by this article.